2010
DOI: 10.1093/molbev/msq205
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of Cytochrome c Oxidase Underlies High-Altitude Adaptation in the Bar-Headed Goose

Abstract: Bar-headed geese (Anser indicus) fly at up to 9,000 m elevation during their migration over the Himalayas, sustaining high metabolic rates in the severe hypoxia at these altitudes. We investigated the evolution of cardiac energy metabolism and O(2) transport in this species to better understand the molecular and physiological mechanisms of high-altitude adaptation. Compared with low-altitude geese (pink-footed geese and barnacle geese), bar-headed geese had larger lungs and higher capillary densities in the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
174
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(183 citation statements)
references
References 59 publications
5
174
2
2
Order By: Relevance
“…Combining these types of approach with more sensitive techniques assaying mitochondrial function directly, such as respiration in isolated mitochondrial preparations (Scott et al 2009), will be valuable in determining whether introgressed mitochondria differ phenotypically from the native type and, ideally, how this might affect whole-animal fitness (reviewed by Dalziel et al 2009 andMelvin 2010). In this way, cases of mitochondrial introgression could potentially be used to link the effects of specific mtDNA mutations in introgressed genetic variants to phenotypic differences (Dalziel et al 2009;Scott et al 2011). …”
Section: Untangling Processes Driving Discordance From Biogeographic mentioning
confidence: 99%
See 1 more Smart Citation
“…Combining these types of approach with more sensitive techniques assaying mitochondrial function directly, such as respiration in isolated mitochondrial preparations (Scott et al 2009), will be valuable in determining whether introgressed mitochondria differ phenotypically from the native type and, ideally, how this might affect whole-animal fitness (reviewed by Dalziel et al 2009 andMelvin 2010). In this way, cases of mitochondrial introgression could potentially be used to link the effects of specific mtDNA mutations in introgressed genetic variants to phenotypic differences (Dalziel et al 2009;Scott et al 2011). …”
Section: Untangling Processes Driving Discordance From Biogeographic mentioning
confidence: 99%
“…For instance, despite the long-held assumption that variation in mtDNA is primarily neutral, a number of studies have identified intra-and interspecific variation in the proteins encoded by genes in the mitochondrial genome that authors have attributed to natural selection (Bazin et al 2006;Meiklejohn et al 2007;Edwards 2009;Ballard & Rand 2005;Ballard & Melvin 2010;Scott et al 2011). If selection for mtDNA variants varies geographically, then discordant patterns between mtDNA and nuDNA can arise (Irwin 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Bar‐headed geese ( Anser indicus ) have a single amino acid substitution in a COX gene that improves the efficiency of oxygen use at high altitudes and enable the geese to fly over the Himalayan Mountains (Scott et al. 2011) while all other species of migratory waterfowl must fly around the mountains. Two lineages of rodents living in hypoxic subterranean habitats independently evolved a shared adaptive configuration of COX genes through different amino acid substitutions (Tomasco and Lessa 2011).…”
Section: Signatures Of Adaptive Divergence In Metazoan Genomesmentioning
confidence: 99%
“…A number of physiological traits increase O 2 uptake, circulation and diffusion to contribute to the remarkable physiological performance of bar-headed geese in hypoxic conditions (Petschow et al, 1977;Perutz, 1983;Jessen et al, 1991;Scott and Milsom, 2007;Scott et al, 2009aScott et al, , b, 2011. Recently, Scott et al (2011) reported variation in cytochrome c oxidase (COX) enzyme kinetics between bar-headed geese and closely related lowland species. This alteration of mitochondrial energy metabolism should be beneficial at high elevations, and may be related to a single amino-acid substitution in subunit three of the mitochondrial cytochrome c oxidase gene (COX3).…”
Section: Hb Polymorphisms In Deer Micementioning
confidence: 99%